Phytochrome and temperature control of seed germination in Muntingia calabura L. (Elaeocarpaceae) - Leite, Idalina T. de A.; Takaki, Massanori [UNESP] (Brazilian Archives of Biology and Technology, 2001)
As sementes de Muntingia calabura L. germinam nas temperaturas de 15 a 35C sendo a temperatura ótima de 35C onde maior número de sementes germinam em menor período. A curva de fluência-resposta demonstra que o fitocromo controla a germinação de sementes através da resposta de fluência baixa. A resposta da semente ao fotoperíodo e à completa inibição pela luz de sombreamento indicam que a espécies coloniza somente clareiras grandes de florestas, confirmando a espécie como pioneira.

The temperature range of germination of seeds of Muntingia calabura L. was 15-35° C and the optimum temperature at 35° C where more seeds germinated at short period. The fluence response curves demonstrated the involvement of phytochrome in the control of germination through the low fluence response. The effect of photoperiod showed that the species need long daily exposures to white light and that shade light inhibited completely seed germination, confirming as pioneer species that colonized only large gaps in the forest.
Keywords: Seed germination; phytochrome; light; temperature; Muntingia calabura